Proximity Violence in Migration Times A Focus in some Regions of Italy, France and Spain - BARTHOLINI, Ignazia Maria (Open Sociology - Open access, 2019)
"This volume, edited by Ignazia Bartholini, principal investigator of the PROVIDE - Proximity on Violence: Defence and Equity project (Rights, Equality and Citizenship Programme - 2014-2020) funded by the EU, shifted the interpretative focus of its research from gender-based to proximity violence. This theoretical intuition-assertion, fruitful too at empirical level, is informed by a wide-scale reconstruction of the phenomenon of migratory violence and corroborated by the results of the action research carried out by six international teams ˗ Ismu, Oxfam, Telefono Donna, Badia Grande, Aseis Lagarto, SamuSocial International, the University of Jaén and the University of Palermo. Systems of protection, formal and informal good practices, as well as critical issues regarding the reception of migrants, are explored and narrated by the co-authors of the volume thanks to the action research they conducted with the collaboration of a plethora of professionals who narrate and illustrate the topic of proximity violence, providing their own particular frames of reference, views and counterfactual reflections. Furthermore, the discussion of legislation provided offers a cogent crosssection of what has been done to contrast the violence which thousands of asylum seekers and refugees undergo and how much national governments need to do in order to host and recognise victims of proximity violence."